Syzygium Polyanthum Wight Leaf Extract Evaluation On Aedes Spp Instar III-IV Larvae - Tri, Widyawati; Ilham, Rizky (Asian Journal of Pharmaceutical Research and Development, 2020)
Aedes spp mosquitos are the vectors that most cause diseases. The rise of insecticide resistance is related to the increasing of vectorial capacity. Plant can be used as an alternative source for controlling these vectors, one of which is Syzygyium polyanthum (Wight). The present study was conducted to investigate the larvasidal properties of S. polyanthum leaf on Aedes spp instar III-IV. Ethanolic extract of S. polyanthum (EESP) was prepared by maceration using ethanol 70%. Larvae were divided into 7 groups (n=25, respectively). Group I to V consisted of different concentrations of EESP (100 (CI);150 (CII);200 (CIII);250 (CIV);300ppm (CV)); VI: Water (W) and VII : Temephos 1% (T). Larvacidal activity was evaluated by calculating the dead larva at 180. 360, 1440 and 2880 minutes to obtain Lethal Concentration 50% (LC50) and Lethal Time 50% (LT50) using Statistical Product and Service Solution (SPSS). The result showed that no larva found dead in W-treated group. Otherwise, the mortality of larva was increased with increasing of EESP concentration (CI to CV). LC50 and LT50 showed 213 ppm and 2410 minutes, respectively. We conclude that EESP has larvicidal activity on Aedes spp instar III-IV. Keywords: Aedes spp, extract, larvicidal, Syzygium polyanthum